The argumentative dimension of geographical discourse in the Qur’anic text - Bekhti, El Ayachi (El Omda in Linguistics and Discourse Analysis, 2024)
There is no doubt that the geographical or spatial discourse of the discourses that have a vision in thinking and to the accuracy of perception and the power of imagination, it is the ambassador of the country, because it expresses the tangible and imagined image of the promotion of sensory and cultural scenes for a country, and the Holy Qur'an is rich in these monuments and spatial archaeological scenes that God made an example for subsequent nations, and the employment of these sensory and visual evidence was not employed in the Qur'anic text arbitrarily, but came under the facts, purposes and purposes moved by the thinking machine Rational in order to clarify the argument, and highlight the dimension of influence and persuasion, because the discourse of a visual sensory nature is closer to the mind of the recipient, as it is not possible and that these spatial scenes remain and witness to the stubbornness, arrogance and disbelief in God practiced by previous nations.